STI service delivery in British Columbia, Canada; providers' views of their services to youth - Masaro, Cindy L (BioMed Central, 2012)
BACKGROUND: Little is known about service providers’ knowledge, attitudes, and experiences in relation to the assessment, diagnosis, and treatment of individuals seeking care for sexually transmitted infections (STIs), and how they influence the delivery of services. The purpose of this study was to explore the perceptions of STI care providers and the ways they approached their practice. METHODS: We used a qualitative approach drawing on methods used in thematic analysis. Individual semi-structured in-depth interviews were conducted with 21 service providers delivering STI services in youth clinics, STI clinics, reproductive health clinics, and community public health units in British Columbia (BC), Canada. RESULTS: Service providers’ descriptions of their activities and roles were shaped by a number of themes including specialization, scarcity, and maintaining the status quo. The analysis suggests that service providers perceive, at times, the delivery of STI care to be inefficient and inadequate. CONCLUSION: Findings from this study identify deficits in the delivery of STI services in BC. To understand these deficits, more research is needed to examine the larger health care structure within which service providers work, and how this structure not only informs and influences the delivery of services, but also how particular structural barriers impinge on and/or restrict practice.